Effects of dietary astaxanthin and ractopamine HCl on the growth and carcass characteristics of finishing pigs and the color shelf-life of longissimus chops from barrows and gilts - Bergstrom, J.R.; Skaar, G.R.; Houser, Terry A.; Tokach, Michael D.; Dritz, Steven S.; Nelssen, Jim L.; Goodband, Robert D.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 160 pigs (initially 198 lb) were used to evaluate the effects of increasing dietary astaxanthin (AX, from Xanthophyllomyces dendrorhous yeast) and Ractopamine HCl (RAC) on the growth and carcass characteristics of finishing pigs as well as the color shelf-life of longissimus muscle (LM) chops from barrows and gilts. Pigs were weighed and randomly allotted to 1 of 8 dietary treatments fed for approximately 26 d preharvest. Dietary treatments consisted of a corn-soybean meal-based control diet, the control diet with 7.5, 15, 30, 60, or 120 ppm AX, and a corn-soybean meal-based diet with 10 ppm RAC and 7.5 or 20 ppm AX. Each treatment had 10 pens, with 2 pigs (1 barrow and 1 gilt) in each pen. A split-plot design with repeated measures was used to compare color characteristics of LM chops from individual barrows and gilts. Overall, pigs fed RAC had increased (P < 0.01) ADG and final BW and improved F/G compared with pigs not fed RAC. Among pigs not fed RAC, F/G improved (quadratic, P < 0.05) and a trend (quadratic, P < 0.06) was observed for increased ADG with increasing AX to 60 ppm. For carcass characteristics, pigs fed RAC had greater (P < 0.03) HCW, 10th-rib LM area, 24-h LM pH, and fat-free lean index (FFLI) than those not fed RAC treatments. Among pigs not fed RAC, a trend (quadratic, P < 0.07) occurred for increased yield with increasing AX. During 6 d of retail display, the initial (d 0) NPPC color score of LM chops from gilts was greater (P < 0.03) than that of chops from barrows. Subjective discoloration scores of LM chops did not differ initially, but increased (linear, P < 0.01) daily and were greater (P < 0.02) on d 6 for chops from barrows and pigs not fed RAC than chops from gilts and pigs fed RAC, respectively (gender × d and treatment × d interactions, P < 0.04). The CIE a* (redness) and CIE b* (yellowness) of LM chops decreased (linear, P < 0.01) during retail display, and chops from gilts and pigs fed RAC had lower (P < 0.04) CIE b* than chops from barrows and pigs not fed RAC, respectively, especially on d 0 (gender × d and treatment × d interaction, P < 0.01). Overall (d 0 to 6), discoloration scores and changes in objective total color were lower (P < 0.02) for LM chops from gilts and pigs fed RAC. These observations suggest that color shelf-life was extended for chops from gilts and pigs fed RAC.
Keywords: Swine; Astaxanthin; Carcass characteristics; Finishing pig; Pork color; Ractopamine HCl